Enhanced lithium storage performance of core-shell structural Si@TiO2/NC composite anode via facile sol-gel and in situ N-doped carbon coating processes. (10th September 2019) - Fang, Rui; Xiao, Wei; Miao, Chang; Mei, Ping; Zhang, Yan; Yan, Xuemin; Jiang, Yu
Abstract: The core-shell structural N-doped carbon encapsulating Si@TiO2 composite (Si@TiO2 /NC) are prepared by facile sol-gel, polymerization of dopamine hydrochloride and the following heat treatment processes, which are confirmed by the scanning electron microscopy, X-ray diffractometer, transmission electron microscopy, X-ray photoelectron spectroscopy and thermogravimetric analyses. The as-prepared Si@TiO2 /NC composite present favorable spherical shape with about 150 nm in diameter and uniform element distribution, and demonstrate the enhanced electrochemical properties compared to the pure silicon, Si@TiO2 and Si/NC materials when the composite materials are used as anodes for lithium-ion batteries, in which the Si@TiO2 /NC composite anodes display the favorable initial coulombic efficiency of 75.9%, remarkable charge specific capacity of 1070.9 mAh g −1 with the coulombic efficiency approaching 100% after 100 cycles under the test current of 200 mA g −1, extraordinary rate and cycle capability with the charge specific capacity of 696.2 mAh g −1 under the test current of 3000 mA g −1 and increased lithium ion diffusion coefficient from 8.179 E-12 cm 2 s −1 to 8.995 E-12 cm 2 s −1 after 100 cycles. Those excellent electrochemical properties can be attributed to the synergistic effect of the robust TiO2 skeleton and the elastic conductive N-doped carbon network, indicating the as-prepared Si@TiO2 /NC composite could be a promising anode for lithium-ion batteries. Graphical abstract: Schematic illustration of the fabrication processes of the Si@TiO2 /NC composite.Image 10345 Highlights: The Si@TiO2 /NC composite are prepared by sol-gel and in situ N-doped carbon coating processes. The TiO2 shell and N-doped carbon coating ensure the stable electrochemical properties. The cell assembled with Si@TiO2 /NC composite demonstrates excellent rate and cycle performance. The composite display high Li + diffusion coefficient and stable microstructure after 100 cycles.